Short‐and long‐term administration of imeglimin counters cardiorenal dysfunction in a rat model of metabolic syndrome. Issue 3 (16th April 2020) - Lachaux, Marianne; Soulié, Matthieu; Hamzaoui, Mouad; Bailly, Anaëlle; Nicol, Lionel; Rémy‐Jouet, Isabelle; Renet, Sylvanie; Vendeville, Cathy; Gluais‐Dagorn, Pascale; Hallakou‐Bozec, Sophie; Monteil, Christelle; Richard, Vincent; et al.
Abstract: Introduction: Imeglimin, a glucose‐lowering agent targeting mitochondrial bioenergetics, decreases reactive oxygen species (ROS) overproduction and improves glucose homeostasis. We investigated whether this is associated with protective effects on metabolic syndrome‐related left ventricular (LV) and vascular dysfunctions. Methods: We used Zucker fa/fa rats to assess the effects on LV function, LV tissue perfusion, LV oxidative stress and vascular function induced by imeglimin administered orally for 9 or 90 days at a dose of 150 mg/kg twice daily. Results: Compared to untreated animals, 9‐ and 90‐day imeglimin treatment decreased LV end‐diastolic pressure and LV end‐diastolic pressure‐volume relation, increased LV tissue perfusion and decreased LV ROS production. Simultaneously, imeglimin restored acetylcholine‐mediated coronary relaxation and mesenteric flow‐mediated dilation. One hour after imeglimin administration, when glucose plasma levels were not yet modified, imeglimin reduced LV mitochondrial ROS production and improved LV function. Ninety‐day imeglimin treatment reduced related LV and kidney fibrosis and improved kidney function. Conclusion: In a rat model, mimicking Human metabolic syndrome, imeglimin immediately countered metabolic syndrome‐related cardiac diastolic and vascular dysfunction by reducing oxidative stress/increased NO bioavailability and improving myocardial perfusion and after 90‐day treatment myocardial and kidney structure, effects that are, at least in part, independent from glucose control. Abstract : This study shows that imeglimin, the 1st representative of the new class of oral antidiabetic agents, glimins, immediately countered metabolic syndrome‐related cardiac diastolic and vascular dysfunction by reducing oxidative stress/increased NO bioavailability and improving myocardial perfusion, and over the long term by countering myocardial and kidney structural modifications, effects that are at least in part, independent from glucose control.